Virulence gene profile and antimicrobial resistance of non-typeable Streptococcus suis isolated from clinically healthy and diseased pigs from North East India - Rajkhowa, Swaraj; Hussain, Isfaqul (Folia microbiologica, 2022)
The present study was conducted to investigate the virulence gene profile and antimicrobial resistance of non-typeable Streptococcus suis isolates circulating in pigs of North East India. Fifty-two non-typeable S. suis isolates from clinically healthy and diseased pigs were screened by using PCR for the presence of the muramidase-released protein (mrp), extracellular factor (epf), hemolysin suilysin (sly), arginine deiminase (arcA), and glutamate dehydrogenase (gdh) genes. Five different virulence gene profiles were observed and the most predominant virulence gene profile found in healthy pigs was mrp- + sly- + arcA- + gdh + + epf- whereas the most predominant virulence gene profile recorded in diseased pigs was mrp+ + sly- + arcA+ + gdh+ + epf-. Significantly lower carrier rate of mrp+ + sly- + arcA+ + gdh+ + epf- virulence gene profile was observed among the isolates from healthy pigs compared to those from diseased pigs (P < 0.05). Antimicrobial resistance patterns of the S. suis isolates revealed fourteen resistance groups (R1 to R14) where 88.46% isolates showed multi-drug resistance. The most predominant resistance pattern observed was CD-COT-E-TE. This is perhaps the first study reporting virulence gene profile and antimicrobial resistance of non-typeable S. suis isolates from pigs in North East India. The occurrence of relatively high levels of resistance of S. suis to some antimicrobials (e.g. macrolides, tetracyclines, and sulphonamides) as observed in the present study may represent a human health concern.
Keywords: Virulence; Animals; streptokokové infekce; India; lidé; Anti-Bacterial Agents; prasata; Swine Diseases; bakteriální léková rezistence; virulence; nemoci prasat; Swine; Streptococcal Infections; Streptococcus suis; zvířata; antibakteriální látky; Drug Resistance, Bacterial; Indie; Humans